PERAN KOMITE SEKOLAH DALAM PENINGKATAN KUALITAS PENDIDIKAN DI SDN 014 KEMPAS JAYA KECAMATAN KEMPAS KABUPATEN INDRAGIRI HILIR RIAU - jurnalmap map (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2022)
This study aims to identify and describe the role of the school committee in improving the quality of education at SDN 014 Kempas Jaya, Kempas District, Indragiri Hilir Regency, Riau. This study uses a qualitative approach to the type of phenomenological research. Sources of data used as sources of information are the head of the School Committee, the Principal, and teachers. Data collection techniques in this study used interviews, observation and documentation. Based on the results of research on the role of school committees in improving the quality of education at SDN 014 Kempas Jaya, Kempas District, Indragiri Hilir Regency, Riau includes: (1) considerations (advisory agency) in determining and implementing education policies at the education unit level; (2) supporting agencies in the form of finance, thoughts and personnel in the implementation of education in education units; (3) controlling agencies in the context of transparency and accountability for the implementation and output of education in education units; (4) mediators between schools with the community in the education unit.